Highly Selective, CRISPR/Cas9‐Mediated Isolation of Genes and Genomic Loci from Complex Genomes by TAR Cloning in Yeast. Issue 8 (9th August 2021) - Kouprina, Natalay; Kim, Jung‐Hyun; Larionov, Vladimir
Abstract: Here we describe an updated TAR cloning protocol for the selective and efficient isolation of any genomic fragment or gene of interest up to 280 kb in size from genomic DNA. The method exploits the special recombination machinery of the yeast Saccharomyces cerevisiae . TAR cloning is based on the high level of in vivo recombination that occurs between a specific genomic DNA fragment of interest and targeting sequences (hooks) in a TAR vector that are homologous to the 5′ and 3′ ends of the targeted region. Upon co‐transformation into yeast, this results in the isolation of the chromosomal region of interest as a circular YAC molecule, which then propagates and segregates in yeast cells and can be selected for. In the updated TAR cloning protocol described here, the fraction of region‐positive clones typically obtained is increased from 1% up to 35% by pre‐treatment of the genomic DNA with specifically designed CRISPR/Cas9 endonucleases that create double‐strand breaks (DSBs) bracketing the target genomic DNA sequence, thereby making the ends of the chromosomal region of interest highly recombinogenic. In addition, a new TAR vector was constructed that contains YAC and BAC cassettes, permitting direct transfer of a TAR‐cloned DNA from yeast to bacterial cells. Once the TAR vector with the hooks is constructed and genomic DNA is prepared, the entire procedure takes 3 weeks to complete. The updated TAR protocol does not require significant yeast experience or extensively time‐consuming yeast work because screening only about a dozen yeast transformants is typically enough to find a clone with the region of interest. TAR cloning of chromosomal fragments, individual genes, or gene families can be used for functional, structural, and population studies, for comparative genomics, and for long‐range haplotyping, and has potential for gene therapy. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of CRISPR/Cas9‐treated genomic DNA for TAR cloning Basic Protocol 2 : Isolation of a gene or genomic locus by TAR cloning Basic Protocol 3 : Transfer of TAR/YAC/BAC isolates from yeast to E. coli